2020
DOI: 10.3389/fphar.2020.586350
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Pharmacology and Gut Microbiota Analysis to Explore the Mechanism of Citri Reticulatae Pericarpium Against Reserpine-Induced Spleen Deficiency in Rats

Abstract: Citri Reticulatae Pericarpium (CRP), dried peels of Citrus reticulata Blanco and its cultivars, is an important traditional Chinese medicine for the treatment of spleen deficiency-related diseases. To date, the mechanism of CRP alleviating spleen deficiency has not been well investigated. This study aimed to explore corresponding mechanisms with integrating pharmacology and gut microbiota analysis. Firstly, the therapeutic effects of CRP against spleen deficiency were evaluated in reserpine-treated rats. CRP w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 59 publications
1
22
0
Order By: Relevance
“… 2019 ; Zheng et al. 2020 ), which is consistent with the applicable scope of MLS. Based on intraperitoneal injection of reserpine, we induced spontaneous sweating symptoms by intraperitoneal injection of pilocarpine.…”
Section: Introductionsupporting
confidence: 74%
“… 2019 ; Zheng et al. 2020 ), which is consistent with the applicable scope of MLS. Based on intraperitoneal injection of reserpine, we induced spontaneous sweating symptoms by intraperitoneal injection of pilocarpine.…”
Section: Introductionsupporting
confidence: 74%
“…For example, GM imbalance and subsequent metabolic changes in patients with qi deficiency affected immunity and energy metabolism, thereby increasing the susceptibility to diseases ( Ma et al., 2018 ). GM in patients with spleen deficiency syndrome ( Peng et al., 2020 ), spleen-yang-deficiency syndrome ( Lin et al., 2018 ), and kidney-yang deficiency syndrome ( Chen et al., 2019 ) had changed, while TCM can help to restore the richness and diversity of GM in specific TCM syndromes ( Zheng et al., 2020 ), which provided insights into the correlation between TCM syndromes and GM imbalance and a new method for further studying the pathogenesis of GM regulating specific TCM syndrome. Two studies have shown that GM can help to distinguish the two TCM syndromes of UC ( Zhang et al., 2019 ) and colorectal cancer ( Wang et al., 2020 ), which can be used as the biological basis for TCM syndrome differentiation and treatment of related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…It exerts potential inhibitory activity on SARS-CoV2 Mpro [ 60 ]. Indeed, multiple chemical compounds in ARND targeted on either ACE2 or 3CLpro, such as kaempferol, luteolin and quercetin from Lonicerae Japonicae Flos (drug 3) [ 61 ], baicalein, wogonin and oroxylin A from Scutellariae Radix (drug 4) [ 62 , 63 ] and naringenin from Citri Reticuulatae Pericarpium (drug 8) [ 64 ]. They manifested anti-inflammatory, immunomodulatory, and free radical scavenging activities through their actions on a multitude of molecules encompassing (Caspase 3) CASP3, IL-6, and mitogen-activated protein kinase (MAPK) 1, 8, and 14, in the signaling pathways of IL-17, NF-κB, TNF and NOS [ 63 , 65 , 66 ] to achieve their anti-COVID-19 mechanisms.…”
Section: Resultsmentioning
confidence: 99%